Wednesday
May 22, 2013

# Homework Help: math

Posted by nevaeh. on Monday, March 15, 2010 at 12:42am.

what is the inverse of (x-3)^2+2
((x-3)squared plus 2))

• math - Reiny, Monday, March 15, 2010 at 8:40am

Do you have a function called

y = (x-3)^2 + 2((x-3)^2 + 2)) ?
then
y = (x-3)^2 + 2(x-3)^2 + 4
= 3(x-3)^2 + 4

to take the inverse,
1. exchange the x and y variables
2. solve the new equation for y

so
x = 3(y-3)^2 + 4
3(y-3)^2 = x-4
(y-3)^2 = (x-4)/3

y-3 = ±√(x-4)/√3
y = 3 ± √(x-4)/√3

• math - drwls, Monday, March 15, 2010 at 10:35am

It looks to me like your wrote the same function twice.

If you meant to write just
y = (x-3)^2 +2, then:
sqrt(y-2) = x-3

x = sqrt(y-2) + 3
and the inverse function is
y = sqrt(x-2) + 3

Related Questions

MATHS - Prove that one over one squared plus one over two squared plus one over ...
math 176 - please detail all the steps for x squared minus 6xy plus 9y squared ...
math - Have 2 questions: 1. Factor Trinomial competely x^2 + 8x + 53 (reads as x...
math - when 3a squared minus 7a plus 6 is subtracted from 4 a squared minus 3a ...
Grade 10 Math - how many integer values are there for K for which 4X squared ...
math - insert grouping symbols into the expression 4 plus 3 times 2 squared plus...
math - 2x squared plus 6 x plus 3 is equal to 0.....
math - How do i find the area of a triangle? For example: A squared + b squared...
math and adding radicals - what is 10 square root of 3u squared plus 6u squared ...